The results of using Нolstein bulls for service in breeding a highly productive herd - Pidpala, T. V.; Zaitsev , Ye. M.; Pravda, A. O. (Scientific Progress & Innovations, 2019)
The purpose of the article is to evaluate the manifestation of economically useful signs of cow-daughters of Holstein breed different servicing bulls. Methods of the research. In the course of the study, commonly used zoo-technical methods (individual accounting of milk productivity, reproductive capacity), laboratory (determining the qualitative milk composition), retrospective analysis (indicators for the entire period of using animals), variation-statistical method (determining sign parameters) were used. The research results. As a result of using bulls for service of Holstein breed in creating a highly productive herd of dairy cattle it has been established that the level of developing productive, reproductive and adaptive properties of cow-daughters is influenced by the origin of the father-parent. The correlation has been established between economically useful signs of cows-firstlings of the Holstein breed of German and Ukrainian selection from various bulls. Regardless of the experimental animals’ origin, there is a high-level positive correlation between the milk yield and the amount of milk fat and protein. The common peculiarity for the offspring of the Holstein breed is the presence of a positive correlation of the low, middle and high levels between the milk yield and the duration of the service period. The differences as to the direction and the degree of correlation dependence between productive and reproductive features of cows-firstlings have been determined, which characterize the diversity of bulls’ influence on their daughters. The elements of scientific novelty. The theoretical and practical propositions for raising the productivity of animals and creating highly productive herds of dairy cattle by using the gene pool of Holstein breed have been further developed. Practical significance. The obtained results should be taken into account in the process of improving the selection during the formation of a highly productive herd of the Holstein breed dairy cattle.